Annual Report of the Park Commissioners of the City of Lynn for the Year Ending December 20, 1892, at 45 (United States: Whitten & Cass 1893 - (:unkn) unknown (General Publisher, 1892)
Prohibited discharge or carry of firearms, except for members of the police force.
--
Keywords: DISCHARGE